Repetitive transcranial magnetic stimulation combined with cognitive behavioral therapy treatment in alcohol-dependent patients: A randomized, double-blind sham-controlled multicenter clinical trial - Hu, Xiaorui; Zhang, Tian; Ma, Hongkun; Zhou, Xuhui; Wang, Hongxuan; Wang, Xiaohong; Cheng, Chang; Li, Yanfei; Duan, Ranran; Zhang, Bo; Wang, Huaizhi; Lu, Jia; et al. (Frontiers in Psychiatry, 2022)
Background: Alcohol dependence (AD) is a complex addictive disorder with a high relapse rate. Previous studies have shown that both repetitive transcranial magnetic stimulation (rTMS) and cognitive behavioral therapy (CBT) may be effective for AD, and we aim to explore more effective treatment options to reduce relapse rates for AD. Methods: A total of 263 AD patients were recruited. They were divided into six groups according to the location and the type of rTMS: left dorsolateral prefrontal cortex (DLPFC), right DLPFC, sham stimulation, and whether they received CBT treatment: with a fixed schedule (C1) and without a fixed plan (C0). There were included in sham rTMS + C0 group (n = 50), sham rTMS + C1 group (n =37), right rTMS + C0 group (n =45), right rTMS + C1 group (n =42), left rTMS + C0 group (n =49), left rTMS + C1 group (n =40). We used OCDS, VAS, ADS, MoCA, GAD-7, PHQ-9, and PSQI to assess alcohol cravings, alcohol dependence, cognition, anxiety, depression, and sleep quality. They were followed up and evaluated for relapse. Results: The sham rTMS + C0 group relapse rate was significantly higher than the right rTMS + C1 group(P=0.006), the left rTMS + C0 group(P=0.031), the left rTMS + C1 group(P=0.043). The right rTMS + C0 group showed significantly higher relapse rate compared to the right rTMS + C1 group(P=0.046). The repeated-measures ANOVA showed an interaction effect between group and time was significant in the rate of PHQ-9 scale reduction(P=0.020). Logistic analysis indicated that smoking and alcohol consumption were independent determinants of relapse (P＜0.05). At twenty-four weeks of follow-up, Kaplan-Meier survival analysis reveal that there is statistically significant relapse rate between six groups (P = 0.025), left rTMS+C1 group has the best treatment effect for alcohol dependent patients. Cox regression analysis confirmed that current smoking, total cholesterol, and total bilirubin (TBIL) level were risk factors of relapse (P＜0.05). Conclusions: This study is the first to suggest that the combination of rTMS and CBT may be a potentially effective treatment for reducing relapse.